Acceptance of clinical artificial intelligence among physicians and medical students: A systematic review with cross-sectional survey - Chen, Mingyang; Zhang, Bo; Cai, Ziting; Seery, Samuel; Gonzalez, Maria J.; Ali, Nasra M.; Ren, Ran; Qiao, Youlin; Xue, Peng; Jiang, Yu (Frontiers in Medicine, 2022)
Background Artificial intelligence (AI) needs to be accepted and understood by physicians and medical students, but few have systematically assessed their attitudes. We investigated the acceptance of clinical AI among physicians and medical students globally to provide guidance for successful implementation into clinical practice. Methods We conducted a two-stage study, involving a foundational systematic review on physician and medical student acceptance of clinical AI. This enabled us to design a suitable web-based questionnaire which was then distributed among practitioners and trainees around the world. Results 60 studies were included in our systematic review, and 758 respondents from 39 countries completed the online questionnaire. Five (62.50%) of eight studies reported 65% or higher awareness about the application of clinical AI. Although, only 10-30% had actually used AI and 26 of 35 studies suggested a lack of knowledge about AI. Our questionnaire found 38% awareness rate and 20% utility rate of clinical AI, and 53% of our sample lacked basic knowledge about clinical AI. 45 studies mentioned attitudes towards clinical AI, and over 60% from 38 (84.44%) studies were positive about it, but they were also concerned about the potential for unpredictable, incorrect results. 77% of the respondents were optimistic about the prospect of clinical AI. The support rate for the statement that AI could replace physicians ranged from 6% to 78% across 40 studies that mentioned this topic. Although, five studies pointed out that efforts should be made to increase collaboration. Our questionnaire showed 68% disagreed that AI would become a surrogate physician, but believed it should assist in clinical decision-making. Participants with different identities, experience and from different countries hold similar but subtly different attitudes. Conclusions Most physicians and medical students were aware of the increasing application of clinical AI, but lacked use experience and related knowledge. Overall, participants have positive but reserved attitudes about AI. In spite of the mixed opinions around clinical AI becoming a surrogate physician, there was a consensus that collaborations between the two should be strengthened. Further education should be conducted to alleviate anxieties associated with change and adopting new technologies.